Success of Intravitreal Ranibizumab for Myopic Choroidal Neovascularization After 2 Years of Treatment. (March 2017) - Abadia, Beatriz; Calvo, Pilar; Ferreras, Antonio; Lopez, Gloria; Leciñena, Jesús; Pablo, Luis; Ruiz-Moreno, Oscar
Purpose: To analyze the anatomical and functional outcomes in patients with choroidal neovascularization (CNV) secondary to pathological myopia (PM). Methods: Retrospective review of the medical records of 40 patients with CNV secondary to PM treated exclusively with intravitreal ranibizumab 0.5 mg and at least 24 months of follow-up. The initial dose comprised 1 or 3 monthly injections followed by a pro re nata regimen. Best-corrected visual acuity (BCVA), central retinal thickness (CRT) measured with spectral domain optical coherence tomography (OCT), and ocular and systemic adverse event were recorded. Results: Mean patient age was 62.5 ± 12.5 years. The mean spherical equivalent refractive error was −12.3 ± 6.9 diopters, and a single intravitreal injection was initially performed in 72.5% of cases. Mean baseline BCVA was 0.33 ± 0.20 logMAR (Snellen equivalent, 20/60), and mean CRT by OCT was 340.65 ± 80 µm. Both BCVA and OCT revealed significant improvement compared to baseline at all established cutoff points ( P < .001). Final BCVA was 0.50 ± 0.3 logMAR (Snellen, 20/40), and final CRT was 255.69 ± 47.7 µm ( P < .001). The mean number of ranibizumab injections was 2.75 ± 1.97. No cases of endophthalmitis or retinal detachments were reported, and no serious adverse systemic events were identified. Conclusion: Excellent anatomical and functional outcomes were obtained after treatment with intravitreal ranibizumab for CNV secondary to PM.